The Journey of Turk Sindbad: Question of Determination the Source of Lithuanian Tatar Texts Written in Slavic Using Arabic Characters - Miškinienė, Galina (Slavistica Vilnensis, 2019)
This article talks about the problem of determining the source of Lithuanian Tatar manuscripts written in Slavic using Arabic characters. Among the sources used by manuscript writers, there should be a clear distinction between Muslim and non-Muslim sources. Surah (chapter) of the Quran, separate Aja (verse), Hadiths, texts about the life of the prophets from different books and prayers were one of the main sources of Arabic insertions. Tora, The Bible, and the Psalms of David are the most popular non-Muslim sources.The goal of our research is to determine the source of The Journey of Turk Sindbad text from the Poltorzicki manuscript (1830). In this article is presented a thorough description of the text. The researcher tells general assumptions regarding the used source, describes the phonetic, lexical, grammatical, graphic, and orthographic peculiarities of the text.
Keywords: Lithuanian Tatars; manuscripts; kitab studies; semi-kitab; textual analysis